Value Added Tax Efficiency in the Western Balkan Countries - Popova, Nelly (UNWE Yearbook, 2021)
An important feature of the tax systems of the Western Balkan countries is the large share of consumption taxes in total tax revenue. Despite its relatively short existence, VAT in particular has proven to be an important fiscal tool, due to its many advantages. The aim of the article is to outline the main developments in VAT in these countries in the past two decades and to analyse its efficiency. The main result of the article is that the tax has good overall revenue performance in the Western Balkans, as measured with the C-efficiency ratio.